Faktor-Faktor Yang Mempengaruhi Pemanfaatan Teknologi, Partisipasi Pemakai Dan Manajemen Puncak Kemampuan Pemakai Terhadap Efektivitas Sistem Informasi Akuntansi - Kiran Maharani; Cris Kuntadi; Rachmat Pramukty (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
In previous research or relevant research it is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that affect the effectiveness of accounting information systems, namely the influence of technology utilization, user participation and top management capabilities of users, a literature study on human resource management. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) the effect of technology utilization on the effectiveness of accounting information systems; 2) user participation affects the effectiveness of the accounting information system; and 3) top management, the ability of users to influence the effectiveness of the accounting information system.